The Use of Window Shopping to Develop Students’ English Vocabulary - Rodhiyah, Kholifah Fitri; Farahdiba, Syarifah; Sofyan, Ryan Rayhana (Journal of Excellence in English Language Education, 2025)
This study aims to determine whether window shopping has the potential to develop students' vocabulary in English, specifically within class VIII D at SMP Negeri 5 Mandai. This study integrates a quantitative methodology with a pre-experimental design. All eighth-grade students are included in the research population, and 31 students from class VIII D serve as a sample, which was selected randomly. To collect the data, a pre-test and post-test design was used, with the pre-test carried out before the treatment (the implementation of Window Shopping) and the post-test conducted afterward. SPSS was used to analyze the data. The use of Window-Shopping improved students’ vocabulary in English, according to the data analysis results. This can be proven by the significant difference shown in the results of the pre- and post-tests. The average pre-test score of the students was 52.7419, and the average post-test score was 89.1935. Since the T-test result was less than P, (0.001 < 0.05) the null hypothesis (H0) in this study is rejected, while the alternative hypothesis (H1) is accepted. Thus, it can be concluded that using Window Shopping as a learning method can enhance students’ English vocabulary.